Energy networks and the law : innovative solutions in changing markets - Roggenkamp, Martha M. (Oxford University Press, 2012)
Energy supply depends on the means of transport to the consumer. Cables and pipelines are necessary to transport oil, gas, and electricity. Their construction and use depend on developments in technology, policies, and laws. This book analyzes the challenges confronting governments, regulators, and network operators in managing energy networks